Max Weber's Economic ethos of the world religions: an analysis - Ertman, Thomas C. (Cambridge University Press, 2017)
This book brings together for the first time in English internationally-recognized specialists who seek to identify what is 'living' and what is 'dead' in the great German social scientist Max Weber's analyses of China, India and Ancient Israel found in his massive, unfinished Economic Ethic of the World Religions. In so doing, the volume offers a powerful new perspective on the current debate concerning the timing of and deeper roots of the 'Great Divergence' - and more recent convergence - in the economic and political development of the West on the one hand, and the great civilizations of Asia on the other. At the same time, this volume also rebalances our understanding of Weber's entire intellectual output by returning The Protestant Ethic and the Spirit of Capitalism to its proper place within Economic Ethic of the World Religions and establishing that work as the equal of the similarly unfinished Economy and Society.